Surgical management of bilateral cataracts in a patient with congenital iris coloboma - Omulecki, Wojciech; Kucharczyk-Pośpiech, Magdalena (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
The term iris coloboma refers to a hole or fissure in the iris from a congenital malformation or an acquired process. Closure defects can involve the iris, ciliary body, lens, retina, choroid and optic nerve. Eyes with congenital colobomata and cataracts are at greater risk for complications during cataract surgery. Dense brunescent cataracts represent a major challenge for surgeons. A 78-year-old patient presented to our office due to visual impairment in both eyes. The visual acuity in the right eye was counting fingers and was 0.2 in the left eye. Iris and chorio-retinal colobomata were seen in both eyes inferiorly. A dense brunescent cataract was present in the right eye and a brunescent but less advanced cataract in the left eye. We decided to perform ECCE in the right eye and phacoemulsification in the left eye. A foldable intraocular lens was implanted in both eyes. Coloboma repair was performed by suturing the iris sphincter with a single polypropylene suture. The vision and photophobia of the patient were improved in both eyes. The best corrected visual acuity was 0.3 in the right eye and 0.5 in the left eye post-operatively. The photophobia has significantly decreased. The patient’s levels of satisfaction and comfort were very good. The surgical treatment of cataracts in eyes with iris coloboma may be very effective. The choice of cataract removal method should be made taking into consideration the cataract severity and nuclear sclerosis. ECCE should be considered in cases with dense brunescent cataracts.